METODE PERTAHANAN EGO TOKOH YUJI ITADORI DALAM ANIME JUJUTSU KAISEN SEASON 1 - Pande Ayu, Ayu Bella Ananda Putri; Ni Luh Gede Meilantari (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2025)
Abstract This article analyzes the ego defense mechanisms employed by Yuji Itadori, the main character in the first season of the anime Jujutsu Kaisen, using Sigmund Freud's theory of ego defense mechanisms. The study explores how Yuji navigates internal and external conflicts arising from his new role as the vessel for Sukuna, the King of Curses. The analysis reveals that Yuji utilizes various ego defense mechanisms, such as repression, sublimation, projection, and displacement, to maintain his psychological balance. This study provides insight into how fictional characters can represent the complexity of human emotions. Keywords: ego defense, personality, literary psychology